Inhibiting Factors of the Acceleration of Irrigation Water Use Improvement Program - Permata, Nadia; Hidayat, Benny; Ophiyandri, Taufika (CIVED, 2025)
Inhibiting Factors of the Acceleration of Irrigation Water Use Improvement Program (P3-TGAI) is a program for rehabilitation, improvement, or construction of irrigation networks based on the participation of farming communities which is carried out in a self-managed or non-contractual manner follow-up to the Ministry of PUPR Directorate General of Water Resources. Based on the evaluation results from Pambudi & Pramujo in 2023, the implementation of P3-TGAI activities at the basic level still encounters various problems, although in general many successes have been achieved. These problems are seen from the aspects of funding transparency, institutional readiness in the field, late determination of target locations, and less than optimal socialization at the farm level. These problems will hamper the aims, objectives, and goals of P3-TGAI activities. In order for the future implementation of this activity to run smoothly, research was conducted to find out what are the inhibiting factors that have the potential to hinder the success of this inhibiting activity in the preparation stage, planning stage, and implementation stage. The research was conducted using a quantitative descriptive method with a questionnaire instrument. The questionnaire was distributed to assistants. From the results of the study, it was found that there were 15 inhibiting factors with a very high influence on the implementation of P3-TGAI activities. 60% of them came from the preparation stage, 27% came from the implementation stage, and the rest (13.3%) came from the planning stage. Of all the inhibiting factors with a very high influence, there is one inhibiting factor with the highest score, namely communication with the community is not good. The solution to poor communication with the community is that the assistants build good emotional relationships with the community, ТPM must often go to the field, and assistants mingle with the community. In terms of general project objectives, inhibiting factors that hinder timeliness are lack of community participation and poor communication and coordination by the community. The inhibiting factors that hinder quality accuracy are the lack of knowledge and experience of the assistants and the lack of socialization to the village community. And the inhibiting factor that hinders cost accuracy is that the community is manipulated by other parties.